2019
DOI: 10.1002/jgh3.12221
|View full text |Cite
|
Sign up to set email alerts
|

Fecaloma presenting as huge abdominal mass

Abstract: Fecal impaction is common in elderly, bed ridden, schizoaffective patients on antipsychotics. Intestinal obstruction due to distal colonic fecaliths is rare as it is amenable to digital manual evacuation and enemas. Our patient presented with abdominal distention, with last bowel evacuation reported 3 months ago. Computed tomography (CT) abdomen demonstrated a huge sigmoid fecalith causing bilateral hydronephrosis. He was managed through laparotomy with sigmoid colon resection and end colostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…[12][13][14] Moreover, patients with schizoaffective disorders who are receiving antipsychotic, anticholinergic, tricyclic antidepressant, and antiserotonergic medication are also at a higher risk. [12][13][14][15] Consistent with these reports, our patient was also bedridden owing to a previous cerebral infarction and femur fracture; she also had a history of chronic constipation. Moreover, her medical records confirmed that the patient had been taking analgesics for the femur fracture.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…[12][13][14] Moreover, patients with schizoaffective disorders who are receiving antipsychotic, anticholinergic, tricyclic antidepressant, and antiserotonergic medication are also at a higher risk. [12][13][14][15] Consistent with these reports, our patient was also bedridden owing to a previous cerebral infarction and femur fracture; she also had a history of chronic constipation. Moreover, her medical records confirmed that the patient had been taking analgesics for the femur fracture.…”
Section: Discussionsupporting
confidence: 86%
“…19,20) Surgery is required only in severe cases. 15) Fortunately, conservative treatment with rectal enema and digital evacuation was successful in our patient.…”
Section: Discussionmentioning
confidence: 57%
“…[3][4][5] Fecaloma can be also be revealed by rectal bleeding, urinary retention and respiratory insufficiency, febrile status, impaired consciousness, altered general condition 7,13,14 Physical examination can demonstrate an abdominal distension, tenderness or mass on palpation and a hard mass in the rectum in digital rectal examination. 7,10,14 In our case, respiratory signs including hypoxemia and pneumonia were the predominant features. The fecaloma was also responsible of urinary retention with renal failure.…”
Section: Discussionmentioning
confidence: 46%
“…[3][4][5] Chronic constipation, frequently seen in elderly and bedridden patients, plays an important role in the development of fecaloma 1,3,4,8 Other common risk factors reported in the literature were neuropsychiatric diseases and use of constipating medication like antiepileptic, antidepressant and opioid therapy. 1,2,7,[9][10][11][12] Fecaloma was also associated with Chagas disease, Hirschsprung's disease, inflammatory and neoplastic diseases, scleroderma, diabetic neuropathy, and anorectal malformations. 2,4,7 The fecaloma's symptoms are various and non-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Fecaloma has varied presentations. Some of the presentations are abdominal mass, stercoral colitis, urinary retention and intestinal obstruction [1] , [5] , [6] , [7] . A systematic review of complications of fecal impaction showed that intestinal obstruction accounts for 13%, while 67% were complications on intestinal wall like perforation, stercoral ulcer [8] .…”
Section: Discussionmentioning
confidence: 99%